The effect of land use change on water turbidity using remote sensing and GIS technique - Ricky Anak Kemarau; Oliver Valentine Eboy; Zaini Sakawi (Journal of Sustainability Science and Management, 2024)
In the context of escalating freshwater pollution and diminishing rainwater collection areas, this investigation utilises remote sensing and GIS to examine the impact of land use and cover (LULC) transformations on water turbidity at Kelalong Dam, Bintulu, Sarawak. Using Landsat 5 Thematic Mapper (TM) and Landsat 8 Operational Land Imager (OLI) plus Thermal Infrared Sensor (TIRS) imagery collected during the lower-rainfall southwest monsoon season (April to September) of 2007 and 2021, the study explores the relationship between LULC shifts and turbidity. The study aims to address the gap in research evaluating the long-term effects of land use on water turbidity, particularly within the Malaysian context. Through the Normalised Difference Turbidity Index (NDTI) and meticulous LULC classification, the repercussions of LULC evolution on water turbidity were analysed. The findings reveal significant LULC alterations over the span, including an increase in built-up areas (25.9 km²), plantations (9.63 km²), and bare lands (0.49 km²), alongside a decline in forests (35.9 km²). These changes correspond with elevated water turbidity levels, highlighting the tangible effects of LULC dynamics on water quality. This study underscores the critical need for enhanced water quality surveillance and prudent LULC management to mitigate river basin pollution.